The Effectiveness of Metacognition Strategy by Snowball Throwing on Student’s Metacognition Ability and Learning Outcomes on Reproduction System Material - Rahayu, Ida Putri; Sukaesih, Sri; Bodijanto, F. Putut Martin Herry (Journal of Biology Education, 2020)
The purpose of this study is to analyze the effectiveness of the application of metacognition strategy by snowball throwing-assisted toward students' metacognitive ability and learning outcomes in reproductive system material. The study design uses Pre-experimental design with a one-shot case study pattern applied to class XI MIPA 4 and XI MIPA 7 of Academic Year 2017/2018. The sampling technique is purposive sampling. Student learning outcomes data are analyzed using classical completeness test. Data on the ability of metacognition is analyzed using a scaled category of metacognition abilities. This study is effective if it is able to reach indicators of effectiveness, namely the average final grade of metacognition ability reaches ≥ 68 with the ok-super scale, and classical completeness of learning outcomes reaches ≥ 85%. Data on metacognition ability is obtained from the value of the monitoring sheet and the value of student learning journals. The metacognitive abilities of the two classes can reach an average final score of 82.45, indicating that students already have awareness in carrying out thinking processes which include the optimal input-elaboration-output stage. Student learning outcomes data obtained from the LDS value, the value of the snowball throwing paper and the posttest value. The learning outcomes of both classes were able to achieve classical completeness on average by 92.5%. The conclusion of this study is the effective snowball throwing-assisted metacognition strategy applied to reproductive system material in SMA N 1 Jakenan.